A MORPHOMETRIC STUDY OF THE POPULATIONS OF HILSA, MILS A ILISHA (HAMILTON) OF THE RIVER HOOGHLY AND OF THE CHILKA LAKE - Pillay, T V R (Indian Journal of Fisheries, 2015)
It is widely suspected thai Hilsa fisheries of India and Pakistan are getting depleted. Suggestions have, therefore, been made by several fishery workers that suitable measures be taken to conserve this important resource. The Indo-Pacific Fisheries Council at its 3rd Meeting at Madras in 1951 and at a Symposium held under its auspices in Calcutta in 1952, considered the problem in some detail and assigned top priority to the study of the Hilsa populations in the countries of Burma, India and Pakistan (I.P.F.C, 1951; Hora, 1954). As the first step in this direction an intensive morphological study of the Hilsa from River Hooghly, which is the type locality of the species, was recommended. After a detailed study of the morphological characters of the stocks in the Hooghly comparison of small samples from other localities was suggested for the purpose of selecting characters likely to be useful in detailed investigations for the delimitation of stocks. The present study was undertaken in pursuance of this recommendation.